2014
DOI: 10.1007/978-3-662-44733-8_53
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of National Culture on Performance Measurement

Abstract: The purpose of the research presented in this paper is to explore the impact of national culture on the design, implementation and use of performance measurement systems (PMS). Managing performance of organizations using management control system or performance management systems is essential for managers. As organizations are increasingly having to expand globally, they are forced to operate their original PMSs, but in different cultures. While, the impact of culture on PMS implementation have been revisited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The successful implementation of a measurement program requires a performance-oriented organizational culture [20].…”
Section: Relevant Aspects Relevant Aspects Intersections Intersection...mentioning
confidence: 99%
See 1 more Smart Citation
“…The successful implementation of a measurement program requires a performance-oriented organizational culture [20].…”
Section: Relevant Aspects Relevant Aspects Intersections Intersection...mentioning
confidence: 99%
“…The strategic implementation of MOOCs makes it possible to contribute, among other things, to improving organizational performance [13,[14][15][16][17][18][19][20][21][22][23].…”
Section: Relevant Aspects Relevant Aspects Intersections Intersection...mentioning
confidence: 99%
“…Clearly, despite significant interest and insight into the influence of national culture on various aspects of management, including management control systems a focused and nuanced understanding of the impact of national culture on PMS is absent. Furthermore, more recent work by Jwijati and Bititci (2014), at early stages of exploring the impact of national culture on PMS, suggest that national culture dimensions impact on different phases of PMS lifecycle in complex ways and highlight the need for further in-depth investigations.…”
Section: Performance Measurementmentioning
confidence: 99%
“…The first stream discusses the impact of corporate culture on PMM in general and states that the relationship between them is dyadic. The second stream suggests that the successful implementation of PMM requires a particular corporate culture (performance-driven culture), and the third direction focuses on specific components of corporate culture (e.g., types of culture) and PMM (e.g., diversity of measurement) (Jwijati and Bititci 2014). Bourne et al (2002), using system dynamics and so-called action research, identified two drivers (management commitment, awareness of the benefits provided by PMM) and four blockers (time and effort, difficulty in implementing performance indicators caused by inappropriate information available from IT systems, resistance to performance measurement, new parent company initiatives) as critical forces influencing the success or failure of PMM implementation.…”
Section: The Impact Of Corporate Culture On Performance Measurement and Management Systemsmentioning
confidence: 99%